Among wolves : Gordon Haber's insights into Alaska's most misunderstood animal - Haber, Gordon C. (University of Alaska Press, 2013)
Alaska's wolves lost their fiercest advocate, Gordon Haber, when his research plane crashed in Denali National Park in 2009. Passionate, tenacious, and occasionally brash, Haber, a former hockey player and park ranger, devoted his life to Denali's wolves. He weathered brutal temperatures in the wild to document the wolves and provided exceptional insights into wolf behavior. Haber's writings and photographs reveal an astonishing degree of cooperation between wolf family members as they hunt, raise pups, and play, social behaviors and traditions previously unknown. With the wolves at risk of bei.